The Main Place Of Linguo-Cultural Studies In World Linguistics And Its Development As A Science (Texas Journal of Multidisciplinary Studies, 2024)
This article is devoted to the study of linguoculturology that is considered a modern science in linguistics. The article reveals the linguoculturological studies that were held by different linguists such as Maslova, Vorobyov, Telia and its emergence as a new science in linguistics. Moreover, there are examples of realia and lacunae which are indispensable part of linguoculturology.